Erratum: Higgs boson mass in supersymmetry to three loops [Phys. Rev. Lett. 100, 191602 (2008)] - Harlander, Robert V.; Kant, Philipp; Mihaila, Luminita; Steinhauser, Matthias (Physical review letters, 2008)
DOI:https://doi.org/10.1103/PhysRevLett.101.039901
Gesehen am 19.11.2018